Kajian Perkawinan Usia Muda di Jawa Timur - Dian Jayantari Putri K Hedo (Pancanaka, 2020)
Early marriage is a long term and serious global problem that needs to be solved in a comprehensive way. Understanding and assessing early marriage can be carried from several points of view, one of them is by understanding psychological aspects and regional context of early marriage. This research will examine early marriage based on Psychosocial Theory and territorial context, especially in East Java region which consists of 9 cities and 29 districts. Early marriages that occurred in East Java will be studied using theory literature and descriptive analysis of routine data that held by BKKBN Provinsi Jawa Timur about early marriages in East Java. This study aims to examine early marriage in East Java based on Psychosocial Theory and regional context, using Literature Study research method. By carrying out this study, it is hoped that early marriage can be prevented, so the quality of population development in East Java can be optimally achieved.